Sporting Event as Strategy of Soft Diplomacy: Case Study 20th National Games (PON XX) Papua, Indonesia - Anugrah, Akhmad Rifky Setya; Harahap, Reiki Nauli; Aviani, Nawang (WIMAYA, 2023)
Indonesia National Sports Games (PON XX) has been successfully held far away from the capital city Jakarta. Located in Papua, PON 20th became the first national sports event hosted in the far east of Indonesia’s province. The agenda is more than just a quadrennial sporting event for the Indonesian Government. The event has become an instrument strategy of soft diplomacy that aimed to deal with domestic and international issues in Papua. This research aimed to discuss the relations between The National Sports Week (PON) XX in Papua and the sports diplomacy for the Indonesian Government to understand development agendas in eastern Indonesia better. The author uses a qualitative study case method to discover how far the sports event can contribute positively towards domestic and international issues of the country. The data source will be gathered from secondary resources, including journals, articles, news, and documents for analysis purposes. The author argues that the National Sports Event (PON) Papua 20th has positively impacted the Indonesian national effort to develop eastern Indonesia.